IDDF2020-ABS-0088 Comparing non-invasive tests for prediction of fibrosis in non-alcoholic fatty liver disease. (18th November 2020) - Siu, Wilson; Onishi, Yusuke; Mukhopadhya, Ashis
Abstract : Background: Non-alcoholic fatty liver disease (NAFLD) is becoming the most common type of chronic liver disease with an estimated worldwide prevalence of 25%. It is a spectrum of disease that ranges from simple steatosis to advanced fibrosis. Non-invasive tests play an important role in identifying patients with fibrosis that require further investigation and follow up. The aim of the study is to evaluate the diagnostic accuracy of different non-invasive scoring tests. Methods: Patients with NAFLD who underwent liver stiffness measurement (LSM) by FibroScan at Aberdeen Royal Infirmary between 2013 and 2016 were retrospectively included in our study. Patients' demographic, clinical and laboratory data were collected closest from the date of the FibroScan. NAFLD fibrosis score (NFS), APRI, FIB-4 and BARD scores were calculated. For this study, clinically significant fibrosis (CSF) is defined as LSM > 7 kPa and advanced fibrosis is defined as LSM >12 kPa. The diagnostic accuracy of the four fibrosis scores was examined by calculating the area under the receiver operating characteristic curve (AUROC). The sensitivity, specificity, positive predictive value and negative value were calculated using optimal cut-offs calculated by Youden index. Results: Of the 863 patients included in this study, 498 (57.7%) were male and the mean age was 54.4 years (SD=14.7). The mean BMI was 32.6 (SD=6.4). 48% of patients had CSF with LSM >7 kPa and 28% had advanced fibrosis with LSM> 12kPa. For CSF, AUROC curve values were: NFS 0.77 (95% CI, 0.73–0.80), FIB-4 0.74 (95% CI, 0.71 -0.78), APRI 0.74 (95% CI, 0.70–0.78) and BARDS 0.65 (95% CI, 0.65–0.74). For advanced fibrosis, the AUROC curve values were: NFS 0.83 (95% CI, 0.80 – 0.87), FIB-4 0.79 (95% CI, 0.75–0.83), APRI 0.75 (95% CI, 0.71 to 0.79) and BARDS 0.75 (95% CI, 0.71–0.79). Conclusions: All fibrosis scores were superior at detecting advanced fibrosis (LSM> 12kPa) compared to CSF (LSM > 7kPa). NFS showed a superior diagnostic accuracy of fibrosis compared to other scores.